2019
DOI: 10.1590/s0102-865020190080000007
|View full text |Cite
|
Sign up to set email alerts
|

Mitigating effect of tanshinone IIA on ventricular remodeling in rats with pressure overload-induced heart failure

Abstract: PurposeTo investigate the effect of tanshinone IIA (TIIA) on ventricular remodeling in rats with pressure overload-induced heart failure.MethodsPressure overload-induced heart failure model (abdominal aortic coarctation) was established in 40 rats, which were divided into model and 5, 10 and 20 mg/kg TIIA groups. Ten rats receiving laparotomy excepting abdominal aortic coarctation were enrolled in sham-operated group. The 5, 10 and 20 mg/kg TIIA groups were treated with 5, 10 and 20 mg/kg TIIA, respectively, f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 28 publications
0
10
0
Order By: Relevance
“… Tanshinone IIA Salvia miltiorrhiza Bunge Pressure-overload 1.5 mg/kg/day, 4 weeks Tanshinone IIA mediates the expression of related molecules by upregulating AMPK and downregulating mTOR to increase autophagy and inhibit apoptosis 168 . Pressure-overload 20 mg/kg/day, 8 weeks Tanshinone IIA reduce inflammatory response and cardiomyocyte apoptosis in HF rats by regulating serum B-type brain natriuretic peptide, interleukin 6 and C-reactive protein levels and myocardial B-cell lymphoma-2 associated X protein levels 169 . 7,8-Dihydroxyflavone / Doxorubicin-induction 5 mg/kg/day, 2 weeks 7,8-Dihydroxyflavone increase cell viability in vitro and reduce doxorubicin-induced cell death.…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 97%
See 1 more Smart Citation
“… Tanshinone IIA Salvia miltiorrhiza Bunge Pressure-overload 1.5 mg/kg/day, 4 weeks Tanshinone IIA mediates the expression of related molecules by upregulating AMPK and downregulating mTOR to increase autophagy and inhibit apoptosis 168 . Pressure-overload 20 mg/kg/day, 8 weeks Tanshinone IIA reduce inflammatory response and cardiomyocyte apoptosis in HF rats by regulating serum B-type brain natriuretic peptide, interleukin 6 and C-reactive protein levels and myocardial B-cell lymphoma-2 associated X protein levels 169 . 7,8-Dihydroxyflavone / Doxorubicin-induction 5 mg/kg/day, 2 weeks 7,8-Dihydroxyflavone increase cell viability in vitro and reduce doxorubicin-induced cell death.…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 97%
“…Polyphenols, such as resveratrol, quercetin, curcumin and epigallocatechin gallate, have obvious protective effects against atherosclerosis, hypertension, myocardial infarction, cardiomyopathy caused by anthracyclines, angiogenesis, and HF 157 . Table 2 158 , 159 , 160 , 161 , 162 , 163 , 164 , 165 , 166 , 167 , 168 , 169 , 170 , 171 , 172 summarizes the polyphenols to treat HF via energy metabolism mechanisms. A large number of polyphenols have been proven to be effective by reducing cardiovascular disease through energy metabolism, but only resveratrol has entered a systematic and standardized clinical trial 173 .…”
Section: Potential Drugs For Reducing Hf By Regulating Energy Metabolismmentioning
confidence: 99%
“…Meanwhile, luteolin improved monocrotaline-induced right VR at least partly through suppressing HIPPO-YAP/PI3K/AKT signaling pathway ( 41 ). Tanshinone IIA may alleviate VR in rats by reducing oxidative stress, inflammatory response, and cardiomyocyte apoptosis ( 42 , 43 ), and enhanced autophagy ( 44 ) via the inhibition of TLR4/MyD88/NF-κB signaling pathway ( 45 ) and activation of SIRT1 signaling pathway ( 43 ). Ongoing STAMP-REMODELING trial, a randomized controlled trial, will provide important clinical evidence on the efficacy of Tanshinone IIA in patients with STEMI that might significantly reduce adverse left VR and potentially improve clinical outcomes ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…Angiotensin II in rat cardiac fibroblasts [114] NOX↓ LPS in mice [115] Astragaloside IV(AS-IV) TRPM7 ↓→Collagen ↓ ISO in rats; Hypoxia or ISO in fibroblasts [116] ROS-mediated MAPK↓ ISO in rat [105] ROS↓→cardiotrophin-1↓→Collagen ↓ ISO in cardiac fibroblasts [117] Ligaturing LAD in rat [98] TXB2↓, PGI2↑ Ligaturing LAD in rat [119] Qishen Yiqi Dripping Pill (QSYQ) NF-κB↓, JAK1↓ and AKT↓ Ligaturing LAD in rats [112] Danhong injection NF-κB↓→TNF-α, IL-1β, and IL-6↓ Ligaturing LAD in rat [120] Tanshinone IIA TLR4-NF-κB↓ Ligaturing LAD in mice [121] SIRT1↑→TNF-α and IL-6↓ TAC in rat [122] Astragaloside IV(AS-IV) TLR4/NF-κB ↓ ISO in rats [96,123] NF-кB signaling ↓, PI3K/AKT↑→TNF-α↓ LPS in mice [124] Ouabain IL-6↓, TNF-alpha↓ LPS in mice [125] Anti-cardiomyocyte death Fuzhengkangfu decoction Bcl-2↑, cleaved caspase-3↓ Doxorubicin in H9C2 [126] Qili Qiangxin Capsule Fas↓, cleaved caspase-3↓ Ligaturing LAD in rat [127] Shengmai injection ER stress↓ →caspase-12↓ Doxorubicin in rat [128] Tanshinone IIA/ Bcl-X↓, cleaved caspase-3↓ Abdominal aortic coarctation in rat, Doxorubicin in cardiomyocyte [129,130] Nrf2↑→p38 and mTOR signaling↓ TAC in mice [131] AMPA↑→Bax, cleaved caspase-3↓ LAD in rat, H2O2 in H9C2 [132] Astragaloside IV(AS-IV) Calpain-1 and ROS ↓→Bcl-2/Bax↑, MMP ↑ ISO in rats or H9C2 cells study showed that Zhenwu Tang delayed ventricular hypertrophy by suppressing the expression of BNP, pextracellular signal-regulated kinase 1/2 (ERK1/2), p-p38 and p-JNK [86].…”
Section: No↑ Enos Phosphorylation↑mentioning
confidence: 99%